Pineal Diffuse Large B-Cell Lymphoma Concomitant With Pituitary Prolactinoma: Possible Correlation Between 2 Distinguished Pathologies: A Case Report. Issue 8 (February 2016) - Kim, Yeong-Jin; Kim, Hee Kyung; Yang, Deok-Hwan; Jung, Shin; Noh, Myung-Giun; Lee, Jae-Hyuk; Lee, Kyung-Hwa; Moon, Kyung-Sub
Abstract : Abstract: This is the first reported case of pineal lymphoma with concomitant prolactin-producing pituitary adenoma. A 51-year-old male experienced worsening headaches accompanied by nausea, diplopia, and memory loss for 1 month. Cranial nerve examination revealed bilateral upward gaze limitation with convergence impairment, which is known as Parinaud syndrome. Magnetic resonance images revealed a mass in the pineal gland with a coexisting mass within the enlarged sella fossa. Hormone analysis revealed hyperprolactinemia. The pineal mass was removed without injuring the hypothalamus, brain stem, or any neighboring vessels. Pathology examination confirmed the diagnosis of diffuse large B-cell lymphoma (DLBCL) involving the pineal gland. After further studies, the pineal lymphoma was determined to be a secondary tumor from a gastric primary tumor. The patient died 6 months after diagnosis due to systemic progression of DLBCL. Although the mechanistic link between hyperprolactinemia and lymphoma progression has not been clarified on a clinical basis, high prolactin levels may contribute to the rapid progression and therapeutic resistance of the lymphoma.